Central control of automotive electronics. (5th August 2014) - Suda, T.; Kumagai, N.
Automotive electronics systems employing microcomputers are increasing at a rapid tempo. Chassis electronics show tendencies toward integration of both similar and different functions into a single system. Engine electronics, aimed specifically at attaining the three targets of greater mileage, cleaner exhaust gas, and improved performance, tend to involve more control items of greater complexity which are processed by making use of the characteristics of the microcomputer. The development of these systems requires a careful study of radio noise interference, idle current at switching power off, back–up circuit for securing system reliability, and the arrangement of a control box. The problems to be solved for completion of these systems in a short period of time concerns the scale and balance of the systems, shortening the manufacturing period of microcomputer mask ROMs, and the selection of system test details.